Safe Motherhood Practices - Bhatt, Shatya Narayan (Rural Development Journal, 2017)
The study on the “Safe Motherhood Practices in Muslim Community of Nepal”. The main objective of the study is to find the knowledge and utilization of safe motherhood practices by the women of reproductive age 15-49 as the target population. The objective of the study is to examine the utilization of prenatal care, postnatal care and care during delivery and also to find out the level of knowledge, attitude, availability and accessibility of safe motherhood services. The main chosen foe this research are Antenatal checkup, TT vaccination, receiving iron and vitamin ‘A’, delivery assistance, place of delivery, use of safe delivery kit, postnatal care and time to health services. Research show that only 47.9 percent received antenatal care, 41.6 percent have received Iron tablets 72.9 percent of respondents have received T.T vaccination and the percent of respondents receiving vitamin 'A' is low that is only 37.5 percent similarly, most respondents (52%) have faced problem during pregnancy. If we observe the situation delivery care of study population 62.5 percent delivery are occurred in house where as 52.2 percent delivery are assisted by TBA. Similarly, 29.1 percent respondents have safe delivery kit. The study show the utilization of postnatal care is high in the study population i.e. 95.9 percent. But more of respondents 41.3 percent are visited TBA.